Performance Analysis of different Anode Materials of a Double Chambered Microbial Fuel Cell - Moinee, Abdullah Al; Sanzida, Nahid (Chemical Engineering Research Bulletin, 2021)
Microbial fuel cells (MFCs) are bio-electrochemical systems (BES) that can oxidize and convert biodegradable wastes directly into electricity via microbial metabolism. Since the oxidation half-cell of an MFC consists of the biodegradable electrolyte and anode, the selection of the right anode materials is essential to optimize the performance of MFCs. Anode acts as the governing support for the growth of biofilm to transfer the electrons. In general, anode materials must have a reasonable surface area for bacterial growth, good conduction, excellent biocompatibility, chemical stability, high mechanical strength, and low cost. In this work, graphite bar, aluminum foil, and carbon cloth were tested as an anode. The comparative performances of them were analyzed in a double chambered MFC containing industrial wastewater with respect to the power density and waste removal efficiency of MFCs. The carbon cloth anode provided better output than graphite bar and aluminum foil. The 10 days of batch operation for carbon cloth anode resulted in a maximum of 672.34 mWm-3 power density and 52.20% removal of chemical oxygen demand (COD). Chemical Engineering Research Bulletin 21(2020) 26-31